PENGARUH PENERAPAN MODEL KLASIKAL TERHADAP HASIL BACAAN AL-QUR'AN TAMAN PENDIDIKAN AL-QUR'AN BAITUL MAKMUR - Ummu Kultsum; Muhammad Ja'far Nashir; Ahans Mahabie (Al'Ulum Jurnal Pendidikan Islam, 2022)
This research is a study to determine the effect of the application of the classical model on the results of reading the Qur'an. This research is a correlational quantitative research that involves collecting data to determine whether there is a relationship and the degree of relationship between several variabels. With a research site at the Baitul Makmur TPA Solo Baru. The subjects of this study took a population of 51 people in 6 existing classes, and the research sample was only taken in 4 large classes at the Baitul Makmur TPA which amounted to 30 people. This research uses observation method, interview method, and questionnaire method with final analysis using product moment correlation using SPSS. This study used data collection through a question instrument which consisted of 15 written questions, a validity test using Aiken's validity test and a reliability test using Cronbach-Alpha. From the results of existing research, it can be concluded that the application of the classical model can be done through 3 methods, namely; lecture method, question and answer method and classical iqra method. The conclusion of the hypothesis test using the Kolmogorov normality test then it is known that the Asymp.Sig (2-tailed) value is 0.200> 0.05, then the Linearity Test which produces ANOVA which produces an F arithmetic value of 0.699<F table 2.64, and hypothesis testing last and using correlation resulted in a calculation with an rcount of 0.382>r table of 0.361. The results of this study indicate that the effect produced in learning with the classical model used on the results of reading the Qur'an is that the classical model makes it easier to start learning and remember learning. This model is the same as other models as one of the models that can make it easier. With repeated repetition, the students will remember it more quickly in everyday life.